Megafires attract avian scavenging but carcasses still persist. (21st August 2021) - Newsome, Thomas M.; Spencer, Emma E.
Abstract: Aim: The effects of fires on vertebrate scavengers have not been characterized despite the importance of scavenging in shaping food web dynamics. We assessed whether the 2019/2020 megafires in Australia shifted the species richness, carcass detection and feeding times of vertebrate scavengers, and whether the fire affected carcasses persistence times. Location: Blue Mountains, south‐eastern Australia. Method: We monitored vertebrate scavengers via remote cameras on a total of 60 experimentally placed kangaroo carcasses for 30 days in two periods before the megafire (January 2018 and 2019) and one period after the megafire (March 2020) in both open and closed canopy habitats. We compared vertebrate species richness, carcass discovery and scavenging activity before and after the fire and between the two habitats. We also assessed carcass persistence (time to carcass removal) before and after the fire and between the two habitats. Results: We collected more than 689, 000 images of nine vertebrate scavengers including six avian, two mammal and one reptile species. We detected no decline in scavenger species richness following the fire, and rates of carcass detection for mammals and reptiles did not differ across pre‐ and post‐fire periods. On the other hand, avian scavengers detected carcasses faster in the post‐fire period and in open compared to closed canopy habitats. Overall, scavengers increased their feeding times in the post‐fire period, especially avian scavengers, but carcasses persisted longer in the post‐fire period when compared to the second pre‐fire period. Main conclusion: Our study identified that a widespread fire could influence avian scavenging dynamics, but that other factors such as habitat and possibly apex scavenger presence affected carcass persistence times over the study period in addition to fire. Future monitoring of carcasses following fires should focus on the responses by both vertebrate and insect scavengers to fully elucidate the effects of these major disturbance events on critical ecosystem processes linked to decomposition.